The Effect Of Corporate Governance On The Performance Of Sharia Maqashid At BPRS In Central Java Period 2016-2020 - Rosiana Nurfadjri Roswan; Darwanto Darwanto (Iqtishodia: Jurnal Ekonomi Syariah, 2021)
Sharia rural bank (BPRS) is a sharia banking that is focused on helping to increase the productivity of micro, small and medium business (UMKM) to aim economic equality, these activities create relationships that exist between banks and stakeholders. This relationship is at risk of agency problems that arise due to differences in interests, so to minimize the occurrence of conflicts of interest, it needs corporate governance to protect the interests of stakeholders and ensure that there are no irregularities in bank operations. This study aims to determine the level of BPRS’s performance in Central Java in achieving maqashid sharia during the 2016-2020 period and to determine the effect of corporate governance on performance maqashid sharia. There are three methods that be used in this study, there are maqashid performance evaluation model (MPEM) used to determine achievement maqashid sharia on the performance of BPRS, the SAW method to determine the order of achievement of maqashid sharia, and panel data regression analysis with the estimation random effect model (REM) used to determine the effect of corporate governance on the performance of maqashid sharia. The results showed that BPRS Artha Leksana (ARL) is a BPRS that gets the first order whose operations are in accordance with maqashid sharia for the 2016-2020 period, while the variables, corporate governance mention that the size of the DPS and the reputation of the DPS have a negative effect, the educational qualifications of the DPS have a positive effect, cross-membership of the DPS, the size of the board of directors and the size of the Independent commissioners have no effect on the performance of maqashid sharia.